Recurrence of anti-MDA5 antibody-positive clinically amyopathic dermatomyositis after long-term remission: A case report. Issue 26 (June 2018) - Endo, Yushiro; Koga, Tomohiro; Ishida, Midori; Fujita, Yuya; Tsuji, Sosuke; Takatani, Ayuko; Shimizu, Toshimasa; Sumiyoshi, Remi; Igawa, Takashi; Umeda, Masataka; Fukui, Shoichi; Nishino, Ayako; et al.
Abstract: Rationale: Among all dermatomyositis (DM) patients, antimelanoma differentiation-associated gene 5 antibody (anti-MDA5 Ab) positive patients have significantly poor short-term mortality, whereas they experience less relapses over the long term after the remission. We report the case of a patient with anti-MDA5 Ab-positive clinically amyopathic dermatomyositis (CADM) with the recurrence of interstitial lung disease (ILD) after 7 years of remission. There has been no case report of an anti-MDA5 Ab-positive DM patient with the recurrence of ILD after 7 years of long-term remission. Patient concerns: A 70-year-old Japanese woman was diagnosed with anti-MDA5 Ab-positive CADM and ILD. After achieving 7 years long-term remission, she was admitted to our department with erythema on the fingers and interstitial pneumonia. Her anti-MDA5 Ab titer was elevated. Diagnoses: We diagnosed recurrent CADM complicated with ILD. Interventions: We successfully treated her with 1, 000 mg of methyl-prednisolone pulse and intravenous cyclophosphamide therapy followed by prednisolone 50 mg/day and an increase of cyclosporine. Outcomes: After that treatment, the patient's skin symptoms and interstitial pneumonia were relieved. All laboratory investigations such as ferritin, the serum markers of interstitial pneumonia (i.e., SP-A, SP-D), and the titer of anti-MDA5 Ab showed signs of improvement. Lessons: Her case suggests that careful physical examinations and monitoring the serum markers are important even after long-term remission is achieved.